KAZAKHSTAN AND ITS INVESTMENT DEVELOPMENT PATH - Zhubikenov, Adil (Copernican Journal of Finance & Accounting, 2022)
Historically, it turned out that the state cannot successfully develop without integration into the global economy. Although such integration is often associated with risks and high costs, these short-term factors overlap with long-term benefits. Foreign direct investment (FDI) is a criterion for this integration, and over the past 30 years, policies in developing countries have been increasingly focused on attracting them. This article attempts to explore the theory of investment development path (IDP according to Dunnings’s theory) of Kazakhstan which economy was considered as transitional, and its key component, the net external investment position, the starting point for data analysis is the beginning of Kazakhstan’s transition to the market system in 1991. The objective of the article is to identify at which stage Kazakhstan is situated. Many studies have been conducted among Western scientists and so far, not a single one among Kazakh scientists. The research was conducted empirically with data mainly from periodic reports published by the United Nations Confederation for Trade and Development (UNCTAD) entitled World Investment Report and studies by the National Bank of Kazakhstan. During the research, the author found out that Kazakhstan is in the second stage of its investment development path. The outcome of the research can be used in the work of state ministries of departments and in the teaching of economic disciplines on investment activities.